First Principle Material Genome Approach for All Solid‐State Batteries - Xu, Hongjie; Yu, Yuran; Wang, Zhuo; Shao, Guosheng (Energy & environmental materials (Hoboken, N.J.), 2019)
Due to ever‐increasing concern about safety issues in using alkali metal ionic batteries, all solid‐state batteries (ASSBs) have attracted tremendous attention. The foundation to enable high‐performance ASSBs lies in delivering ultra‐fast ionic conductors that are compatible with both alkali anodes and high‐voltage cathodes. Such a challenging task cannot be fulfilled, without solid understanding covering materials stability and properties, interfacial reactions, structural integrity, and electrochemical windows. Here in this work, we will review recent advances on fundamental modeling in the framework of material genome initiative based on the density functional theory (DFT), focusing on solid alkali batteries. Efforts are made in offering a dependable road chart to formulate competitive materials and construct “better” batteries. A summary of methods as an integrated material genome approach. The tasks for theoretical simulation/modeling are classified into two categories for the predictions of (A) thermodynamic and dynamic stability and (B) performance of SSE or ASSB.